Analisa Tebal Perkerasan Lentur pada Ruas Jalan Waikelo-Karoso Sepanjang 1km Kabupaten Sumba Barat Daya - Dairo, Yoseph Bulu ; Suhudi; Arifianto, Andy Kristafi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Conditions at the Planning Study Site Thickness of Flexible Pavement in Waikelo-Karoso Sta 47 + 000-Sta 48 + 000 Southwest Sumba District with 1,000 m of road length are lack of road access, drainage and lighting. The purpose of the study was to determine the flexible pavement thickness, the dimensions of the channel and the budget for the STA 47 + 000-STA 48 + 000 waikelo-karoso road. Data collection methods are used by conducting observations and direct surveys at locations in the form of primary data and secondary data. From the analysis results obtained thickness of pavement consisting of bottom foundation (sub base) thickness of 20 cm, aggregate B of upper foundation (base cours) thickness of 20 cm, aggregate class A layer of surface (surface) 10 cm Laston. The water debit obtained for the channel capacity on the road is 0.192 m3 / sec, with the channel discharge obtained 0.201 m3 / sec. From the results of the recapitulation of the budget plan, the costs obtained based on the analysis data for each work item include preparation work Rp. 629,347,950, mobilization and demobilization of Rp. 19,800,000, land works and paving Rp. 2,109,983,228.62, the work of a partner and drainage plastering Rp. 355,698,397.18. With the 1 km road length studied, obtained pavement thickness, channel dimensions, and cost budget respectively, ie 20 cm thick, channel dimensions with a channel width of 0.55 m, channel height of 0.275 m, with a budget of Rp. 3,426,321,000.